80 Evaluation of the trusight oncology 500 assay for routine clinical testing of tumor mutational burden (TMB) and clinical utility for predicting response to pembrolizumab. (10th December 2020) - Wei, Bo; Kang, John; Kibukawa, Miho; Arreaza, Gladys; Maguire, Maureen; Chen, Lei; Qiu, Ping; Lang, Lixin; Aurora-Garg, Deepti; Cristescu, Razvan; Levitan, Diane
Abstract : Background: Various biomarkers have been investigated for their ability to identify patients more likely to respond to immunotherapy. Recently, the PD-1 inhibitor pembrolizumab was approved by the FDA for treating patients with unresectable or metastatic solid tumors with high TMB (TMB-H) who have no satisfactory alternative treatment options following progression on prior treatment. The FDA contemporaneously approved the FoundationOne®CDx (F1CDx; Foundation Medicine) as the companion diagnostic for TMB assessment for pembrolizumab. However, multiple comprehensive genomic profiling panels that can measure TMB are currently available or in development. We evaluated the performance of TruSight™ Oncology 500 (TSO500; Illumina) for assessing TMB and its clinical utility using F1CDx and whole exome sequencing (WES) as reference methods. Methods: Pretreatment archival tumor samples from patients enrolled in 8 clinical trials of pembrolizumab monotherapy were evaluated for TMB by TSO500, F1CDx QSR pipeline v3.2.0, and WES. Correlation was assessed using Spearman's rank correlation coefficient (ρ). The F1CDx and WES TMB cutpoints were 10 mut/Mb and 175 mut/exome, respectively. The TSO500 cutpoint was selected using the Youden index criterion. Concordance was assessed by calculating area under the receiver-operating curve (AUROC), positive percentage agreement (PPA), and negative percentage agreement (NPA). Statistical significance of the association of TMB measured by TSO500 with ORR was assessed using logistic regression adjusted for ECOG performance status and cancer type. Clinical utility of the selected TSO500 TMB cutpoint for discriminating responders and nonresponders was assessed by calculating sensitivity, specificity, positive predictive value, negative predictive value, ORR enrichment, and prevalence. Results: TMB scores were valid for 294/294 patients assessed by TSO500, 269/270 assessed by F1CDx, and 293/294 assessed by WES. TMB assessed by TSO500 had good correlation with TMB assessed by F1CDx (ρ=0.76) and WES (ρ=0.74). Using Youden index criterion, 10 mut/Mb was the TSO500 cutpoint that corresponded with both the F1CDx and WES cutpoints. TSO500 reliably predicted TMB-H and non–TMB-H status as determined by the F1CDx (AUROC=0.99, PPA=97.4%, NPA=93.0%) and WES (AUROC=0.95, PPA=76.2%, NPA=96.1%) cutpoints. TMB measured by TSO500 was significantly associated with ORR (one-sided P<0.0001). Clinical utility metrics were generally similar for TSO500 and F1CDx (table 1 ) and TSO500 and WES (table 2 ). Conclusions: TMB assessed by TSO500 is highly correlated and concordant with TMB assessed by F1CDx and WES. Similar to the validated and approved F1CDx TMB cutpoint of 10 mut/Mb, the TSO500 TMB cutpoint of 10 mut/Mb is predictive of response to pembrolizumab monotherapy. Acknowledgements: This analysis and all included studies were sponsored by Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Trial Registration: NA Ethics Approval: The protocols and all amendments for the studies included in this analysis were approved by the appropriate ethics committee at each participating institution. Consent: NA Reference: NA